Socio-technical-economic characterization of cocoa production systems in the Manabí province micro-regions - Ecuador - Guillén, Saskia; Urdaneta, Fátima; Portillo, Elvis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Cocoa production systems vary depending on regional conditions and agronomic and post-harvest management practices that impact cocoa quality. This descriptive study was conducted to characterize the cocoa production systems of the microregions of Manabí Province, Ecuador, in their social, technical, and productive dimensions. This study is important because it allows us to understand the differential characteristics of cocoa production systems in Manabí, facilitating decision-making to improve the productivity and quality of Ecuadorian cocoa, a strategic product for the national economy. To this end, a sample of 150 producers was taken from the northern, central, and southern regions of Manabí, who were then administered a questionnaire. Cross-tabs were compiled across regions with the frequencies or means of the calculated indicators, and X2 tests or analysis of variance (depending on the type of variable) were applied. Results allowed for the identification of characteristics specific to each microregion; however, the producers in the South stood out with higher productivity and average income, since they are directly dedicated to cultivation, work on mostly legally registered properties, planted mainly with “Nacional” cocoa, which is propagated by seed, and also use irrigation but keep few records of the production process; they stand out for carrying out the entire post-harvest process, a determining factor in the best productive outputs since they obtained the best price related to the quality of their cocoa.